Sustainability Design Considerations for Timber-Concrete Composite Floor Systems - Md Abdul Hamid Mirdad; Hossein Daneshvar; Thomas Joyce; Ying Hei Chui (Advances in Civil Engineering)
Over the last few decades, there has been growing interest in the use of low-carbon materials to reduce the environmental impacts of the construction industry. The advent of mass timber panels (MTP), such as cross laminated timber (CLT), has allowed structural engineers to specify a low-carbon material for a variety of floor design considerations. However, serviceability issues such as vibration and deflection are limiting the construction of longer span timber-only floor systems and have encouraged the development of timber-concrete composite (TCC) systems. The use of concrete would negatively impact on the carbon footprint of the TCC floor system and should be minimized. The purpose of this study was to study the impact on embodied carbon in the TCC system, when the ratio of timber and concrete was varied for specific floor spans. Two MTP products were considered, CLT and glued laminated timber (GLT). The floors were designed to satisfy structural, acoustic, and vibration criteria, and the results were presented in the form of span tables. It was found that using thicker MTP instead of adding concrete thickness to meet a specific span requirement can lead to lower embodied carbon values. Increasing concrete thickness for long-span floor systems led to a reduction in allowable floor span due to the vibration criterion being the controlling design parameter. Increasing timber thickness also resulted in higher strength and stiffness to weight ratios, which would contribute toward reducing the size of lateral load resisting systems and foundations, resulting in further reductions in the embodied carbon of the entire structure.